2019
DOI: 10.1051/e3sconf/201911101089
|View full text |Cite
|
Sign up to set email alerts
|

Design methodology for combined production and distribution for domestic hot water and space heating

Abstract: As local heat demand is reducing due to an increased insulation rate, investing in sustainable heat production becomes less interesting. Nevertheless a substantial demand of heat remains in which the thermal energy needed for the generation of domestic hot water grows relatively in importance. In the last two years standards to size production and distribution systems were revised and methods based on tap patterns were elaborated. Nevertheless, some aspects were not covered yet, e.g. how to deal with decentral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In [32], it was found that the locations of the temperature sensors had a larger influence on lowering the return temperature than controlling the charging flow rate ( ṁch ). Nonetheless, a lower ṁch reduced the return temperature by 5 to 8 • C. In [33], the control strategy of [32] was further optimised to lower the peak demand in the DH and lower the return temperatures by up to 16.4 • C. Additionally, other researchers stated that the design has a major impact on energy performances [34,35]. Lyu et al [36] stated that the size of the central storage tank has a large influence on the efficiency of the central HP.…”
Section: Present Control Strategies In Collective Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…In [32], it was found that the locations of the temperature sensors had a larger influence on lowering the return temperature than controlling the charging flow rate ( ṁch ). Nonetheless, a lower ṁch reduced the return temperature by 5 to 8 • C. In [33], the control strategy of [32] was further optimised to lower the peak demand in the DH and lower the return temperatures by up to 16.4 • C. Additionally, other researchers stated that the design has a major impact on energy performances [34,35]. Lyu et al [36] stated that the size of the central storage tank has a large influence on the efficiency of the central HP.…”
Section: Present Control Strategies In Collective Heatingmentioning
confidence: 99%
“…To size the central energy system, the new sizing method for CHDCs [53] was used, which was recently validated in [54]. The sizing method gives all possible combinations of thermal power in kW and "active" storage capacity in kWh to meet the peak heat demand.…”
Section: Central Energy System Models: Ghp and Boilermentioning
confidence: 99%